Newly synthesized peripherally octa-substituted zinc phthalocyanines carrying halogen terminated phenoxy-phenoxy moiety: comparative photochemical and photophysical features - Kirbac, Erkan; Erdogmus, Ali (Tubitak Scientific & Technological Research Council Turkey, 2020)
This study reports the 3 new phthalonitrile derivatives, namely 4, 5 Bis-[4-(4-bromophenoxy) phenoxy]phthalonitrile (1), 4,5 Bis-[4-(4-chlorophenoxy) phenoxy]phthalonitrile (2), and 4, 5 Bis[4-(4-fluorophenoxy) phenoxy]phthalonitrile (3). Their octa-substituted zinc phthalocyanines (4, 5, 6) are reported for the first time in this study. The resulting compounds were characterized by utilizing some spectroscopic methods, such as UV-Vis, (HNMR)-H-1, FT-IR spectroscopy, as well as mass spectraand elemental analysis. To show photosynthesizer's potential, emission (F-F), singlet oxygen (O-1(2)), and photodegradation quantum yields (Phi(Delta), Phi(d)) of octa-peripherally phthalocyanines (Pcs) were performed in the solutions, such as biocompatible solvent UMW (dimethyl sulfoxide) as well as DWI (dimethylformamide) and THE (tetrahydrofuran). Solvent and octa-peripherally binding effect of the halogen (Br, Cl, F) terminated phenoxy-phenoxy groups on phthalocyanine rings for photophysicochemical properties (4, 5, and 6) were compared with the tetra-peripherally and tetra nonperipherally substituted derivatives. The new dyes (4 to 6) may be evaluated in photodynamic therapy (PDT) of cancer as photosensitizers due to efficient O-1(2) from 0.55 to 0.75.
Keywords: Photochemistry; photophysics; zinc phthalocyanine; octa-substituted; halogen substitution; QUANTUM YIELDS; PHOTOSENSITIZERS; DERIVATIVES; SOLVENT; CHLORO; Chemistry; Engineering